(3JPcQI Chdi GdCdHGH hGdLGeY GdYLH GdYLGHs - (3OGhO Hf YeQ GdHUjQ GdCfWGcj, J (B1008 (3g` s ((3LHd dHfGf s)
(3ChdgG (B:s
(3cJGH OGhO GdCfWGci HYOO OjHGLI Whjdg jbhd GdeUfa hSejJg HJPcQg Chd GdCdHGH hGdLGeY GdYLH GdYLGH hQJHJg Ydi ebOeI heNRfI hCQHYI CHhGH hNGJeI GdHGH GdChd ai cdjGJ gPG GdYde hGdeONd Edjg s
(3BNQgG (B:s
(3MQa GdjGA jGSejf hjbGd HGdhGh jeGe GdTafjf Je GdHGH GdKGdK s
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ HGdMeQIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs